IQ Motif Containing GTPase-Activating Protein 3 (IQGAP3) Inhibits Kaempferol-Induced Apoptosis in Breast Cancer Cells by Extracellular Signal-Regulated Kinases 1/2 (ERK1/2) Signaling Activation - Hu, Gaowu (Med Sci Monit, 2019)
BACKGROUND: Breast cancer (BC), a prevalent and heterogeneous disease of glandular breast tissue, is the most common cancer in women. The interaction between Kaempferol and IQ motif containing GTPase-activating protein 3 (IQGAP3) in BC and its underlying mechanism are poorly defined. MATERIAL/METHODS: After natural phytochemicals treatment, the expression of IQGAP3 in BC cells (ZR-75-30 and BT474) was detected by real-time PCR. Then, the proliferation and apoptosis in BC cells with different gradient concentrations (10, 25, 50, and 100 μmol/l) of Kaempferol treatment were detected. After treatment with Kaempferol or epidermal growth factor (EGF), we assessed apoptosis and expression of related genes. RESULTS: We found that natural phytochemicals, especially Kaempferol, decreased IQGAP3 expression in BC cells. Kaempferol significantly induced proliferation inhibition and apoptosis in BC cells, concurrent with decreased IQGAP3 expression. Upregulation of IQGAP3 inhibited apoptosis in BC cells, along with increased expression of phosphorylated extracellular signal-regulated kinases 1/2 (p-ERK1/2) and B cell lymphoma 2 (Bcl2) and decreased Bcl-2-associated X protein (Bax) expression, which was counteracted by Kaempferol treatment. EGF markedly inhibited Kaempferol-induced apoptosis in BC cells, and ERK1/2 inhibitor PD98059 had an effect similar to that of Kaempferol. CONCLUSIONS: IQGAP3 may be a potential target gene for Kaempferol in the treatment of BC, and upregulation of IQGAP3 inhibits Kaempferol-induced apoptosis in BC cells by ERK1/2 signaling activation. Targeting IQGAP3 may contribute to the study of natural phytochemicals as anti-tumor drugs in BC.